Medical treatment of hemorrhoids - Gutiérrez Blanco, Horacio (Cirugía del Uruguay, 1973)
It must be etiopathogenic, aimed at correcting predisposing factors, such as dilation of the hemorrhoidal plexuses and reducing the time of the upright position and improving the precipitating factors, such as permanent or transient increase in hypertension of these plexuses, anitis, and sphincter hypertonia.